Evaluation of Regional Spatial Development on Landslide and Flood Prone with Actual Site Conditions in Kendari City - Aldiansyah, Septianto; Ningsih, Duwi Setiyo Wigati; Saputra, Randi Adrian (Jurnal Wilayah dan Lingkungan, 2023)
Kendari City is an area that has a high level of vulnerability to landslides and floods. The high intensity of rainfall and the geomorphological form of the area make Kendari City almost every year landslides and floods occur. This study aims to analyze the distribution of landslide and flood susceptibility and its suitability to the actual situation and evaluate the spatial pattern plan, especially in settlement areas. The method used is survey-based scoring and weighting. Overlay technique used in this study on physical variables including geological conditions, slope, rainfall, land use, soil type and distance from the river. The results show that areas in Kendari City are prone to landslides and floods respectively 79.33% and 81.75% with variations in the level of moderate and high vulnerability. Moderate vulnerability dominates in both disasters with an area of 165.80 km2 and 165.70 km2. The suitability between the map and the actual situation reached 80.63% and 91.30%. Most of the spatial pattern plans, especially settlements that have been made and determined by the government, are appropriate for regional development in Kendari City. Evaluation of spatial patterns of landslide and flood prone zones shows that a small proportion of high vulnerability zones are in the delineation of settlement areas with suitability levels reaching 93.05% and 76.45%.